Dietary Lycium barbarum polysaccharide modulates growth performance, antioxidant capacity, and glucolipid metabolism in largemouth bass (Micropterus salmoides) fed with high- carbohydrate diet - Qi, Long; He, Yuyun; Zhong, Guofang (Frontiers in Marine Science, 2025)
To investigate the ameliorative effects of Lycium barbarum polysaccharide (LBP) on growth performance, oxidative stress, and glucolipid metabolism in largemouth bass (Micropterus salmoides) fed with high-carbohydrate diets. Fish (41.81 ± 0.36) g were fed on high-carbohydrate diets (15% α-starch) supplemented with 0% (15% α-Starch and no LBP, HLBP), 0.2g/kg LBP (LBP0.2), 0.4g/kg LBP (LBP0.4), 0.6g/kg LBP (LBP0.6) and 0.8g/kg LBP (LBP0.8) for 56 days. An additional low-carbohydrate (10% α-starch) dietary group (10% α-Starch and no LBP, NLBP) was set up and fed for the same 56 days. The final body weight (FBW), weight gain ratio (WGR), and specific growth rate (SGR) of fish in the LBP0.6 group were the highest, and the treatment groups were all significantly higher than in the HLBP group (P < 0.05). The activities of AMS, LPS, and TPS in the intestine and liver were all highest in the LBP0.6 group and significantly higher than in the HLBP group (P < 0.05). In the intestine and liver, the activities of T-AOC, CAT, GSH-PX, and SOD were significantly higher in the LBP0.6 and LBP0.8 groups than in the HLBP group (P < 0.05). The expression of CAT, SOD, and GPX genes were highest in the LBP0.8 group and significantly higher than in the HLBP group (P < 0.05). In the intestine and liver, the expression of IL-1β, IL-8, and TNF-α genes were significantly lower in the LBP0.4, LBP0.6, and LBP0.8 groups than in the HLBP group (P < 0.05); the expression of IL-10 and TGF-β1 genes were significantly higher in the LBP0.6 and LBP0.8 groups than in the HLBP group (P < 0.05). The expression of GK, PFK, and G6P genes were significantly higher in the LBP0.6 and LBP0.8 groups than in the HLBP group (P < 0.05). The expression of ACC, CPT-1, and FAS genes were significantly higher in the LBP0.4, LBP0.6, and LBP0.8 groups than in the HLBP group (P < 0.05). In summary, the addition of 0.6 g/kg LBP was effective in ameliorating the negative effects of a high-carbohydrate diet on largemouth bass.